Comparison of probiotics with different concentrations on the growth and survival rate of Bonylip Barb (Osteochilus vittatus) - Fatimatus Saadah; Ratna Djuniwati Lisminingsih; Husain Latuconsina (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2023)
Bonylip barb (Osteochilus vittatus) is one of Indonesia's local fish which is starting to bloom in cultivation. One of the important needs in the development of fish farming is feed, to increase feed efficiency by providing probiotics which play a role in increasing growth, survival rates, digestibility, feed efficiency, the immune system and the composition of beneficial bacteria in the digestive tract of fish. This study aims to compare the concentration of different probiotics in commercial feed on the growth and survival of barley nilem (Osteochilus vittatus). The research was conducted at Pandaan Aquaculture Installation (IPB), Pasuruan Regency, East Java. Experimental study using a completely randomized design (CRD) with four treatments and three replications. Statistical analysis to compare growth performance (length and weight) and survival of nilem fish used analysis of variance (ANOVA) test. The results showed that there were differences in the growth of weight, length, and survival of barley nilem (Osteochilus vittatus) on commercial feed with different concentrations of probiotics. Where there is a tendency that the higher the concentration of probiotics in commercial feed, the higher the growth in length and weight and survival of nilem fish (O. vittatus).